Analysis of Inkjet Printed Catalyst Coated Membranes for Polymer Electrolyte Electrolyzers. Issue 7 (1st January 2018) - Mandal, Manas; Valls, Antoni; Gangnus, Niklas; Secanell, Marc
Abstract : Inkjet printing (IJP) is studied as a novel fabrication method for catalyst coated membranes (CCMs) for polymer electrolyte electrolyzers. IrO2 and Pt/C inks were deposited by IJP over the membrane to fabricate anode and cathode electrodes, respectively. Optical microscopy, scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) were used for ex-situ surface and thickness characterization of the anode catalyst layer (CL). SEM images show the CL is uniform and well adhered to the membrane. EDX images show even distribution of the catalyst and ionomer in the CL. Hydrogen cross-over, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests were performed to estimate hydrogen cross-over, double layer capacitance (C dl ) and cell resistances. Cross-over results show that the membrane is not damaged during printing. A kinetic study revealed Tafel slopes similar to those in literature. Electrochemical performance tests showed that inkjet printed electrolyzer CCMs achieved 1 and 2 A/cm 2 current densities at average potentials of 1609 mV and 1696 mV (NRE211) and average of 1743 mV and 1977 mV (N117) respectively. The electrolyzer performance improved slightly when the printing piezo-voltage decreased but with a cost of higher fabrication time. The stability of the electrode was inline with literature data. The proposed electrodes outperform most of the previously reported electrolyzer data in the literature using commercial IrO2 catalyst.